THE RELATIONSHIP BETWEEN BLOOD LEAD LEVELS AND HEMOGLOBIN LEVELS IN MINING WORKERS IN MOROSI: BLOOD LEAD LEVELS AND HEMOGLOBIN - Kartini, Sapril; Teguh, Ririn; Sanatang, Sanatang; Oktavia, Elin (STIKes Mandala Waluya Kendari, 2025)
Background: Lead disrupts heme synthesis through various mechanisms, one of which is by interfering with the activation of the enzyme δ-aminolevulinic acid dehydratase (δ-ALAD) and ferrochelatase. Lead contamination in the blood will decrease hemoglobin levels; the higher the lead concentration in a person's body, the lower their hemoglobin levels will be. The purpose of this study is to determine the relationship between lead (Pb) levels in the blood and hemoglobin levels in miners in the nickel processing industry. Methods: This study uses an analytical research type with a cross-sectional design employing the Atomic Absorption Spectroscopy (AAS) and Hematology Analyzer methods. The population in this study consisted of 16 respondents. The sample in this study consisted of 15 respondents. The variables of this study are miners, lead (Pb) levels, and hemoglobin (Hb) levels. Results: The study obtained an average blood lead level of 13.81 µg/dL and an average hemoglobin level of 13.4 g/dL. The research results with the Pearson correlation statistical test between blood lead levels and hemoglobin levels showed a significance of p = 0.404 and a correlation coefficient of r = -0.233. Conclusion: Based on this study, it is concluded that there is no relationship between blood lead levels and hemoglobin levels in nickel processing industry mine workers, with a correlation between lead (Pb) and hemoglobin of p = 0.404, which is greater than 0.05 (p > 0.05).